2012
DOI: 10.1038/ng.1064
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific analysis of chromatin state identifies temporal signatures of enhancer activity during embryonic development

Abstract: Chromatin modifications are associated with many aspects of gene expression, yet their role in cellular transitions during development remains elusive. Here, we use a new approach to obtain cell type-specific information on chromatin state and RNA polymerase II (Pol II) occupancy within the multicellular Drosophila melanogaster embryo. We directly assessed the relationship between chromatin modifications and the spatio-temporal activity of enhancers. Rather than having a unique chromatin state, active developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
520
4
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(560 citation statements)
references
References 69 publications
32
520
4
4
Order By: Relevance
“…Despite the variance, however, there was a significant trend for enhancers to have higher H3K27me3 levels in the uninduced versus active state (P < 10 −2 , Wilcoxon rank-sum test) (Fig. 3B), consistent with previous findings (Bonn et al 2012).…”
Section: H3k27me3 Is Not a Good Marker For Uninduced Enhancers Or Seqsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the variance, however, there was a significant trend for enhancers to have higher H3K27me3 levels in the uninduced versus active state (P < 10 −2 , Wilcoxon rank-sum test) (Fig. 3B), consistent with previous findings (Bonn et al 2012).…”
Section: H3k27me3 Is Not a Good Marker For Uninduced Enhancers Or Seqsupporting
confidence: 90%
“…Most open enhancer regions are marked by histone monomethylation on lysine 4 of histone H3 (H3K4me1), but only active enhancers carry lysine 27 acetylation on histone H3 (H3K27ac) (Creyghton et al 2010;Ernst et al 2011;Rada-Iglesias et al 2011;Zentner et al 2011;Bonn et al 2012). Since some inactive enhancers show activation during later development, the combination of H3K4me1 along with low H3K27ac at inactive enhancers was termed the poised enhancer signature (Creyghton et al 2010;Rada-Iglesias et al 2011).…”
mentioning
confidence: 99%
“…The increase of DNA methylation in CpG sites located in the enhancer regions is particularly striking because enhancer activity is known to be anticorrelated with DNA methylation and is highly cell type-specific (Heintzman et al 2009;Stadler et al 2011;Bonn et al 2012). We have also previously shown that repressed genes may have permissive enhancers that can initiate cell-fate reprogramming in fibroblasts (Taberlay et al 2011), but what we observe in the intestinal epithelium illustrates another side in the complex regulation of cell identity.…”
Section: Discussionmentioning
confidence: 99%
“…Because enhancer activity has been associated with transcription of enhancer RNAs (eRNAs) (16,(18)(19)(20)(21) we analyzed the density of nuclear long and short RNA on enhancers from RNA-seq experiments in MCF7 cells (Methods). We found that AGO1-bound enhancers have significantly higher density of long nuclear RNAs relative to enhancers without significant AGO1 signal (P < 0.005) (Fig.…”
Section: Ago1 Preferentially Associates With Active Enhancers But Doementioning
confidence: 99%